Recombinant Adeno-Associated Virus Serotype 9 Gene Therapy in Spinal Muscular Atrophy - Kotulska, Katarzyna; Fattal-Valevski, Aviva; Haberlova, Jana (Frontiers in Neurology, 2021)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease caused by deletion or mutation of the SMN1 gene. It is characterized by a progressive loss of motor neurons resulting in muscle weakness. The disease affects 1 in 11,000 live births and before the era of treatment SMA was a leading genetic cause of mortality in infants. Recently, disease modifying therapies have been introduced in clinical practice. They include intrathecal and oral antisense oligonucleotides binding to pre-mRNA of SMN2 gene and increasing the translation of fully functional SMN protein as well as SMN1 gene replacement therapy. Onasemnogene abeparvovec uses the adeno-associated virus 9 (AAV9) vector to deliver the SMN1 gene. Phase 1 and phase 3 clinical trials showed that a single administration of onasemnogene abeparvovec resulted in improvement of motor functions in the majority of infants with SMA. Currently, phase 3 trials in SMA1 and SMA2 patients, as well as presymptomatic infants diagnosed with SMA, are ongoing. The drug was approved for medical use in the US in 2019, and in Japan and the European Union in 2020. Thus, first real-world data on efficacy and safety of onasemnogene abeparvovec in SMA patients are available.